Analisis Dampak Pernikahan Dibawah Umur di Desa Falabisahaya Perspektif Hukum Islam - Samsudin Buamona B; Sunardi Tomia (Sekolah Tinggi Agama Islam Babussalam Sula, 2024)
This study aims to analyze the impact of child marriage in Desa Falabisahaya from an Islamic law perspective. A qualitative field research method was employed. The findings indicate that underage marriages comply with the requirements and regulations of Islamic marriage and fulfill half of the functions of marriage, namely the biological function. However, underage marriage has more negative than positive impacts. For instance, the lack of mental preparedness among the couple often leads to disputes and jeopardizes marital harmony. Additionally, other negative impacts include health risks, school dropout, and the potential for divorce. Moreover, underage marriage falls short in terms of psychological aspects, maturity of thought, and financial readiness to build a household. Keywords: Child marriage, Islamic law